Multi-layered structures for lightweight providing shielding from unintended radiation exposure for pediatric patients. (March 2023) - Kwon, D.E.; Han, D.H.; Kim, J.O.; Jung, K.H.; Baek, C.H.
Abstract: The field of medical radiation shielding aims to minimize unnecessary radiation exposure. However, lead-based materials have significant drawbacks including toxicity, heavy weight, thickness, and poor flexibility. It is beneficial to replace lead with ecofriendly materials that have similar shielding performance. According to previous research, most manufacturing methods are biased towards mixing metallic nanoparticles with polymer, which leads to an uneven radiation shielding ratio. This study evaluates the physical properties of single pure elements such as half-value layer, linear attenuation coefficient, and mass attenuation coefficient using a Monte Carlo Simulation. It also present the combination of material and thickness with several new multi-layered structures in the radiation range of 60 ㎸ – 90 ㎸. The simulation results indicate that at 60 ㎸, a combination of tungsten (30% of shielding performance) and bismuth (65% of shielding performance) has a weight reduction rate at 40.80% compared to a combination of bismuth (30% of shielding performance) and tungsten (65% shielding performance). At 90 ㎸, the weight of tungsten (70% of shielding performance) and bismuth (25%) has decreased about 21.73%. Also, the combination of a relatively high-density element and lower element is more effective than using a material with a mono-layered structure. Considering characterization with a continuous X-ray beam spectrum, bismuth with high atomic number that leads to high weight is placed in the first sheet, which absorbs the high energy range. Relatively lower atomic number materials such as tin or tellurium is placed after bismuth, which leads to shielding the rest of the energy range and reducing the total weight. Further, this feature is expected to contribute to reducing the radiation dose to pediatrics patients, making it meaningful to verify the shielding performance with the use of single elements. Highlights: The multi-layered shielding system with effective shielding performance. The shielding sheets doesn't have harm effect. Combination and order of materials play an important role of the weight.